Iron Metabolism in Liver Cancer Stem Cells - Recalcati, Stefania; Correnti, Margherita; Gammella, Elena; Raggi, Chiara; Invernizzi, Pietro; Cairo, Gaetano (Frontiers in Oncology, 2019)
Cancer stem cells (CSC) which have been identified in several tumors, including liver cancer, represent a particular subpopulation of tumor cells characterized by properties similar to those of adult stem cells. Importantly, CSC are resistant to standard therapies, thereby leading to metastatic dissemination and tumor relapse. Given the increasing evidence that iron homeostasis is deregulated in cancer, here we describe the iron homeostasis alterations in cancer cells, particularly in liver CSC. We also discuss two paradoxically opposite iron manipulation-strategies for tumor therapy based either on iron chelation or iron overload-mediated oxidant production leading to ferroptosis. A better understanding of iron metabolism modifications occurring in hepatic tumors and particularly in liver CSC cells may offer new therapeutic options for this cancer, which is characterized by increasing incidence and unfavorable prognosis.